Plan tecnológico estratégico para el desarrollo de la infraestructura del sector turístico de Portoviejo - Briones Pacheco, Miguel Humberto (2023)
The objective of the research was to propose a strategic technological plan that contributes to the development of the infrastructure in Portoviejo's tourism sector. Three phases were proposed for the research, which were fundamental to obtain the results, using analytical and descriptive methods taking as a reference methodology the "Strategic Planning for the evaluation of an Intelligent Tourist Destination". In phase one, a diagnosis was made of the tourism system where the study area was characterized, obtaining results about the main economic activity, which is the textile trade. In addition, the information was concretized with the analysis of the tourism system, focusing the synthesis with the technological contribution of the components. In the second phase, studies of supply, demand and public management were carried out through questionnaires in relation to the components of an intelligent tourist destination, in the application of surveys and an interview with the Department of Tourism, to know the perspective of the actors directly involved with tourism, a description that served to propose strategies through a SWOT matrix, where strengths, opportunities, weaknesses and threats were assessed. Finally, in the third phase, strategies were designed, taking as a model the components for an intelligent tourist destination, focusing the guidelines with the tourism system, for which the benefits that Portoviejo would obtain in order to improve the technological infrastructure were identified. Likewise, short-, medium- and long-term objectives were developed based on the vision and mission. Finally, a matrix of objectives was developed in order to identify the main objectives and strategies to achieve the goals during the four-year planning period.